Characterization and photocatalytic study of tantalum oxide nanoparticles prepared by the hydrolysis of tantalum oxo-ethoxide Ta8(μ3-O)2(μ-O)8(μ-OEt)6(OEt)14 - Ambreen, Subia; Pandey, N D; Mayer, Peter; Pandey, Ashutosh (Beilstein Journal of Nanotechnology, 2014)
Ta8(μ3-O)2(μ-O)8(μ-OEt)6(OEt)14 (1) was obtained by the controlled hydrolysis of tantalum ethoxide Ta(OEt)5 in the presence of ammonia. Compound 1 is considered as the intermediate building block in the sol–gel polymerization of Ta(OEt)5. Further hydrolysis of compound 1 yielded nanoparticles of Ta2O5, which were characterized by various techniques such as TGA-DTA-DSC, UV–vis DRS, XRD, SEM, TEM, particle size analyzer (DLS) and the Brunauer–Emmett–Teller (BET) method. The band gap of the particles was calculated by using the Tauc plot. The photocatalytic activity of Ta2O5 nanoparticles was tested by the degradation of the organic dye rhodamine B.
Keywords: bandgap; tantalum-oxo-ethoxide; Tauc plot; tantalum pentoxide (Ta2O5)

(untitled) - Hubert-Pfalzgraf, L. G. (Inorg. Chem. Commun., 2003)

(untitled) - Pollard, K. D.; Puddephatt, R. J. (Chem. Mater., 1999)

(untitled) - Bradley, D. C. (Chem. Rev., 1989)

(untitled) - Ambreen, S.; Gupta, K.; Singh, S.; Gupta, D. K.; Daniele, S.; Pandey, N. D.; Pandey, A. (Transition Met. Chem., 2013)

(untitled) - Yanovsky, A. I.; Turova, N. Y.; Korolev, A. V.; Chebukov, D. E.; Pisarevsky, A. P.; Struchkova, Yu. T. (Russ. Chem. Bull., 1996)

(untitled) - Bradley, D. C.; Gaze, R.; Wardlaw, W. (J. Chem. Soc., 1957)

(untitled) - Day, V. W.; Eberspacher, T. A.; Klemperer, W. G.; Park, C. W.; Rosenberg, F. S. (J. Am. Chem. Soc., 1991)

(untitled) - Schmid, R.; Mosset, A.; Galy, J. (J. Chem. Soc., Dalton Trans., 1991)

(untitled) - Abrahams, I.; Bradley, D. C.; Chudzynska, H.; Motevalli, M.; O'Shaughnessy, P. (J. Chem. Soc., Dalton Trans., 2000)

(untitled) - Bradley, D. C.; Gaze, R.; Wardlaw, W. (J. Chem. Soc., 1955)

(untitled) - Bradley, D. C.; Carter, D. G. (Can. J. Chem., 1961)

(untitled) - Bradley, D. C.; Holloway, H. (Can. J. Chem., 1962)

(untitled) - Nashed, R.; Hassan, W. M. I.; Ismail, Y.; Allam, N. K. (Phys. Chem. Chem. Phys., 2013)

(untitled) - Ezhilvalavan, S.; Tseng, T. Y. (J. Mater. Sci.: Mater. Electron., 1999)

(untitled) - Sayama, K.; Arakawa, H. (J. Photochem. Photobiol., A: Chem., 1994)

(untitled) - Zou, Z.; Ye, J.; Sayama, K.; Arakawa, H. (Nature, 2001)

(untitled) - Takahara, Y.; Kondo, J. N.; Takata, T.; Lu, D.; Domen, K. (Chem. Mater., 2001)

(untitled) - Kominami, H.; Miyakawa, M.; Murakami, S.; Yasuda, T.; Kohno, M.; Onoue, S.; Kera, Y.; Ohtani, B. (Phys. Chem. Chem. Phys., 2001)

(untitled) - Murase, T.; Irie, H.; Hashimoto, K. (J. Phys. Chem. B, 2004)

(untitled) - Yang, X.; Xu, L.; Yu, X.; Li, W.; Li, K.; Huo, M.; Guo, Y. (Colloids Surf., A, 2008)

(untitled) - Sreethawong, T.; Ngamsinlapasathian, S.; Suzuki, Y.; Yoshikawa, S. (J. Mol. Catal. A: Chem., 2005)

(untitled) - Gömpel, D.; Tahir, M. N.; Panthöfer, M.; Mugnaioli, E.; Brandscheid, R.; Kolb, U.; Tremel, W. (J. Mater. Chem. A, 2014)

(untitled) - Pandey, A.; Roy, M. K.; Pandey, A.; Zanella, M.; Sperling, R. A.; Parak, W. J.; Samaddar, A. B.; Verma, H. C. (IEEE Trans. NanoBiosci., 2009)

(untitled) - Malčić, V. D.; Mikočević, Z. B.; Itrić, K. (Tech. Gaz. - Univ. Osijek, 2011)

(untitled) - Yang, L.; Kruse, B.; Miklavcic, S. J. (J. Opt. Soc. Am. A, 2004)

(untitled) - Licht, S.; Khaselev, O.; Ramakrishnan, P. A.; Soga, T.; Umeno, M. (J. Phys. Chem. B, 1998)

(untitled) - Tauc, J.; Grigorovici, R.; Vancu, A. (Phys. Status Solidi, 1966)

(untitled) - Sánchez-Vergara, M. E.; Alonso-Huitron, J. C.; Rodriquez-Gómez, A.; Reider-Burstin, J. N. (Molecules, 2012)

(untitled) - Murphy, A. B. (Sol. Energy Mater. Sol. Cells, 2007)

(untitled) - Yakuphanoglu, F.; Ilican, S.; Caglar, M.; Caglar, Y. (J. Optoelectron. Adv. Mater., 2007)

(untitled) - Byrappa, K.; Subramani, A. K.; Ananda, S.; Rai, K. M. L.; Dinesh, R.; Yoshimura, M. (Bull. Mater. Sci., 2006)

(untitled) - Zhu, Y.; Yu, F.; Man, Y.; Tian, Q.; He, Y.; Wu, N. (J. Solid State Chem., 2005)

(untitled) - Sehested, J. (J. Catal., 2003)